Novel halogen free hydrophobic trioctylammonium-based protic ionic liquids with carboxylate anions: Synthesis, characterization, and thermophysical properties - Al Kaisy, G.M.J. (Elsevier B.V., 2017)
A three novel hydrophobic trioctylammonium-based protic ionic liquids (PILs) with 3,4-dimethylbenzoate, salicylate, and nonanedioate anions were synthesized and their structure were confirmed using nuclear magnetic resonance, elemental analysis and Fourier transform infrared spectroscopy. The three synthesized PILs were liquids at room temperature. The thermal properties were determined using thermogravimetric analyzer and differential scanning calorimetry. Density, viscosity, surface tension, and refractive index were measured for the synthesized PILs at temperature between 293.15 and 363.15 K at atmospheric pressure and as expected, it was found to decrease with increasing temperature. The density measurements were correlated as a linear function of temperature, and the viscosities were fitted to a Vogel-Fulcher-Tamman equation. The density measured values were used to calculate the molar volume, molecular volume, standard entropy, lattice potential energy and the isobaric thermal expansion coefficients, whilst the surface excess energy and entropy were calculated using the measured surface tension data. The di-cationic nonanedioate PIL was found to have higher viscosity, surface tension, heat capacity and onset decomposition temperature. © 2017 Elsevier B.V.